2005
DOI: 10.1029/2003wr002443
|View full text |Cite
|
Sign up to set email alerts
|

Coping with unreliable public water supplies: Averting expenditures by households in Kathmandu, Nepal

Abstract: [1] This paper investigates two complementary pieces of data on households' demand for improved water services, coping costs and willingness to pay (WTP), from a survey of 1500 randomly sampled households in Kathmandu, Nepal. We evaluate how coping costs and WTP vary across types of water users and income. We find that households in Kathmandu Valley engage in five main types of coping behaviors: collecting, pumping, treating, storing, and purchasing. These activities impose coping costs on an average household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
172
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 161 publications
(194 citation statements)
references
References 21 publications
8
172
2
2
Order By: Relevance
“…Our study was similar to other reports [9,17], which showed that the duration of the piped water supply pre-GEQ was very short (four hours weekly), and which further shrank to 2.3 h post-GEQ. Piped water consumption varied depending upon the altitude of the location and the KUKL branches.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study was similar to other reports [9,17], which showed that the duration of the piped water supply pre-GEQ was very short (four hours weekly), and which further shrank to 2.3 h post-GEQ. Piped water consumption varied depending upon the altitude of the location and the KUKL branches.…”
Section: Discussionsupporting
confidence: 81%
“…This could be attributed to the drastic reduction in piped water consumption post-GEQ because use of alternative water sources is a coping strategy [15,17] to supplement the inadequate piped water amount. Similar to the impact on piped water consumption, the occurrence of the GEQ affected groundwater and jar water consumption reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the methods described in the literature to compute coping costs due to inadequate water and sanitation services 15 and the private costs of waterrelated illnesses. 34 For both sets of computations, time was valued at one-half of the village-level gender-specific average hourly wage.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] "Revealed preference" studies, on the other hand, measure economic benefits by examining actual preventive behaviours, such as treating the water. [13][14][15][16][17][18][19]26,27 Particular types of revealed preference studies 15,16 known as avoided or coping cost studies -thus named because they examine the prevention costs incurred to cope with poor water and sanitation -measure the savings in prevention costs resulting from improvements in water and sanitation.…”
Section: Introductionmentioning
confidence: 99%